Penggunaan Metode Structural Equation Modeling (SEM) Pada Pengaruh Kemampuan Kerja dan Motivasi Terhadap Kinerja Karyawan serta dampaknya Terhadap Kualitas Layanan Administrasi Pendidikan di Fakultas Ekonomi dan Bisnis Universitas Bina Insan - Surajiyo, Surajiyo; Nasruddin, Nasruddin; Fanira, Nosi; Paleni, Herman (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
This study aims to obtain results about the effect of work ability on employee performance, motivation on employee performance, work ability on service quality, motivation on service quality, work ability on service quality through performance, and motivation on service quality through performance in the Undergraduate Education Program. (S1) Faculty of Economics and Business Management and Accounting Study Program, with a total population of students who are active in the Even Semester of the Academic Year 2020/2021 as many as 1148 students. The number of samples taken using the Slovin formula and an error rate of 5% (0.05), obtained a sample of 297 students. The distribution of the questionnaires was carried out offline and online (google form).Stages of research by conducting observations, grouping observational data, searching references/literatures, making frameworks and hypotheses, determining data collection techniques, making research instruments or questionnaires, distributing questionnaires both offline and online (google form), analyzing data using the Structural Equation Modeling (SEM) with a computer tool Lisrel 8.70 program. The steps of Structural Equation Modeling (SEM) carried out by Confirmatory Factor Analysis (CFA), model identification, and Modification of the Model as well as the Goodness of Fit Index.The results showed that the coefficient of the effect of work ability on performance was 0.68, and the t-count value was 7.91. Because the value of t arithmetic is 7.91 > 1.96, then work ability has a significant effect on employee performance. Thus, it can be interpreted that the higher the work ability, the higher the employee's performance. The value of the coefficient of the influence of motivation on performance is 0.20, and the t value is 2.87. Because the t value is 2.87 > 1.96, motivation has a significant effect on employee performance. Thus, it can be interpreted that the higher the motivation, the higher the employee's performance. The coefficient value of the effect of work ability on service quality is 0.82, and the t-count value is 8.62. Because the value of t count is 8.62 > 1.96, the work ability has a significant effect on service quality. Thus, it can be interpreted that the higher the work ability, the higher the service quality. The value of the coefficient of the influence of motivation on service quality is 0.16, and the t-count value is 2.45. Because the value of t count is 2.45 > 1.96, then the effect of motivation on service quality is significant. Thus, it can be interpreted that the higher the motivation, the higher the service quality. The coefficient value of the effect of performance on service quality is 0.46, and the t-count value is 5.72. Because the t value is 5.72 > 1.96, the direct effect of performance on service quality is significant. Thus, it can be interpreted that the higher the performance, the higher the service quality. The value of the coefficient of the effect of work ability on service quality through performance can be seen from the magnitude of the indirect effect of work ability on service quality through performance of 0.32 with a t value of 8.62 > 1.96. This shows that motivation is able to be a mediating variable by 32% for the relationship between work ability and service quality. While the value of the coefficient of the influence of motivation on service quality through performance can be seen from the magnitude of the indirect effect of motivation on service quality through performance of 0.08 with a t value of 2.45 > 1.96. This shows that performance is able to be a mediating variable of 8% for the relationship between motivation and service qualityÂ Keywords: Work Ability, Motivation, Performance, Service Quality